Agricultural Development and Regional Income Dynamics in Uzbekistan - Murodil Isroiljonov (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis examines the relationship between agricultural development and disposable income growth across 13 regions of Uzbekistan during 2011–2024 using panel-data econometric methods. The empirical findings reveal a positive and statistically significant relationship between agricultural growth and regional income growth. The results also indicate that nationwide macroeconomic conditions played an important role in shaping regional income dynamics during the study period. Overall, the findings suggest that agricultural development remains an important contributor to regional economic growth and household welfare in Uzbekistan.